2007
DOI: 10.1021/jf063143z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gluten-Forming Polypeptides. 1. Biosynthesis of Gliadins and Glutenin Subunits

Abstract: Five winter wheat cultivars--GK Othalom (HMW-GS composition 2*, 7+8, 5+10), Ukrainka (1, 7+8, 5+10), Palotás (2*, 7+9, 5+10), Ködmön (2*, 7+8, 5+10), and Csongrád (2*, 7+9, 2+12)--grown in Hungary and harvested in the year 2005 were studied. The biosynthesis of gluten-forming polypeptides was followed starting at the 12th day after anthesis to the 53rd. Fresh kernel weight, moisture, and dry matter content of fresh kernels and gliadin and glutenin contents were determined. Gliadin components, total amounts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The explanations given for this include that the changes in glutenin synthesis during the later stages of kernel maturation occur largely due to a reduced protein synthesis invoked by Fusarium infection and the inhibition of protein synthesis by the accumulation of DON [5,8,11]. In contrast, another study found no gliadin and glutenin monomer synthesis at diVerent maturation stages; just polymeric glutenin formation was detected in the later stages [12].…”
Section: The Inxuence Of Fusarium Infection On the Quantitative Protementioning
confidence: 96%
See 1 more Smart Citation
“…The explanations given for this include that the changes in glutenin synthesis during the later stages of kernel maturation occur largely due to a reduced protein synthesis invoked by Fusarium infection and the inhibition of protein synthesis by the accumulation of DON [5,8,11]. In contrast, another study found no gliadin and glutenin monomer synthesis at diVerent maturation stages; just polymeric glutenin formation was detected in the later stages [12].…”
Section: The Inxuence Of Fusarium Infection On the Quantitative Protementioning
confidence: 96%
“…A change in the synthesis behaviour at diVerent maturation stages has been postulated as an explanation for this observation [11]. Studies focusing on the synthesis of cereal seed storage proteins did not show any alterations in the synthesis stages during grain maturation; only a belated polymerization of glutenins was noted [12]. An inXuence of Fusarium infection on LMW glutenin degradation has been shown in a study which focused on suboptimal storage conditions [13].…”
Section: Introductionmentioning
confidence: 99%
“…A change in the synthesis behaviour at different maturation stages has been postulated as an explanation for this observation [11]. However, a study focusing on the synthesis of cereal seed storage proteins did not show any alterations in the synthesis stages during grain maturation; only a belated polymerization of glutenins was noted [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the grain productivity is a major concern for wheat growers, millers are interested in the functional properties of flour. Thus, there have been many attempts to predict final wheat product quality in the early stages of kernel development (Abonyi et al, 2007;Dupont et al, 2000;Greene et al, 1985;Iametti et al, 2006;Johansson et al, 1994;Ng et al, 1990;Uhlen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As described above, several authors have studied compositional changes in gluten proteins during kernel development (Abonyi et al, 2007;Bartels and Thompson, 1986;Greene et al, 1985;Grimwade et al, 1996;Iametti et al, 2006;Johansson et al, 1994;Mecham et al, 1981;Ng et al, 1990;Skerritt et al, 1988). However, relatively few studies have examined individual gluten proteins at the subunit level.…”
Section: Introductionmentioning
confidence: 99%